New records of home range of Tonkin snub-nosed monkey (Rhinopithecus avunculus Dollman, 1912) in Khau Ca forest, Ha Giang province - Hoang, Thach Mai; Covert, Herbert H. (Academia Journal of Biology, 2012)
The Tonkin snub-nosed monkey presently is known from four small and isolated populations in Tuyen Quang province (Na Hang and Cham Chu district) and Ha Giang province (Khau Ca and Tung Vai of Quan Ba district). It is listed as “Critically Endangered” in the IUCN’s red list of threatened animals, and as one of the top 25 most endangered primates of the world [10]. This study focused on reviewing previous research on home range size in Vietnam and daily range length of TSNM in Khau Ca area, Ha Giang province. According to Fleagle (1999), the home range of a primate or primate group consists of the day ranges or daily path lengths, that the primate or group uses over a long period of time. Among primatologists this period is usually a year. A day range or daily path length is the distance that an individual or a group moves in a single day (or night). Primate groups frequently use one part of their home range more intensively than others and “this heavily used area is called the core area” [3: 52]. By plotting the day ranges or daily path lengths that occur throughout the year on a map, primatologists can determine the home range of a primate group. Maps of home ranges can help primatologists understand the extent of a species range and document the areas where their species of interest can and cannot inhabit. Knowledge of home ranges and resource use by primates are critical for effective conservation measures. Estimates of the home range of TSNM vary among authors. Le Hien Hao (1973) identified the home range of this species as 1.7 to 3.14 km2. Pham Nhat (1993) reported the average size of home range as 4.55 km2 (Table 8) while Boonratana and Le Xuan Canh (1994, 1998) reported a home range of about 10 km2 for the TSNMs in Tat Ke sector, Na Hang Nature Reserve (Tuyen Quang province). Further, most encounters in Khau Ca are inside the core area of 7 km2. The aim of this study is to calculate the daily range length of the TSNM population that inhabits the Khau Ca forest, Ha Giang province. Ranging data were collected in May-June, 2008 during a 28 day field season. These data were the result of seven encounters and 26 contact hours with free-ranging R. avunculus groups. Day range lengths were 851.3 m (1st June, 2008) and 673.5 (10th June, 2008).